RECONSTRUCTION OF CRIMINAL SANCTIONS FOR PERPETRATORS OF BUSINESS CRIMES - Doni Hendra Lubis; Ida Hanifah; Adi Mansar (Faculty of Law, Universitas Pekalongan, 2023)
The development of criminal liability in Law Number 1 of 2023 concerning the Criminal Code differentiates in detail the form of liability for individual legal subjects with legal entities. The regulation specifically for criminal liability for legal subjects in the form of legal entities (corporations) is contained in paragraph 3 of Article 45 to Article 50 of Law Number 1 of 2023 concerning the Criminal Code. As the principle of the case before the law, the new Criminal Code in terms of law enforcement against legal subjects in the form of corporations also adheres to the reasons for the elimination of criminal penalties (justification and excuse) as contained in Article 50 which states that in essence justification and excuse apply in the corporate criminal liability system as long as the reasons are directly related to the criminal act being prosecuted